Batas Toleransi Maksimal Laju Alir Gas Umpan dengan Konsentrasi Co2 Konstan pada Mikroalga (Tetraselmiss Chuii dan Spirrulina Sp) dalam Fotobioreaktor - Elida Purba; Sakha Abdussalam; Agus Rivaldy K. (Inovasi Pembangunan : Jurnal Kelitbangan, 2017)
This study discusses the determination of flow rate limits given to the Tetrashelmis chuii and Spirrulina sp microalgae against their resistance in terms of adsorbing CO2 with a considerable concentration of CO2 feed. The purpose of this study was to determine the tolerance limit of feed gas flow rate with constant CO2 concentration in microalgae (Tetraselmiss chuii and Spirrulina sp) in a photobioreactor. It is necessary to characterize the type of microalgae against its resistance in receiving a given gas feed to reduce the amount of CO2 by varying the feed flow-rate of the photobioreactor at 1 l/min, 1.5 l/min and 2 l/min with a CO2 concentration of 33 % . It was found that the optimum flow rate possessed by microalgae is best in the absorption of CO2, Spirrulina sp with a flow rate capability of 1 l/min with absorption of 83.13 % compared to Tetraselmis chuii with a flow rate of 1.5 l/min with absorption of 76.10 %